1998
DOI: 10.1210/jcem.83.9.5131
|View full text |Cite
|
Sign up to set email alerts
|

Are Autoimmune Thyroid Dysfunction and Depression Related?1

Abstract: The objective of this study was to examine the relationship between autoimmune thyroid disease and depression in perimenopausal women. Thyroid function [TSH, free T4, and thyroid peroxidase antibodies (TPO-Ab)] and depression (using the Edinburgh Depression Scale) were assessed cross-sectionally together with other determinants of depression. The subjects were 583 randomly selected perimenopausal women (aged 47-54 yr) from a community cohort of 6846 women. The main outcome measures were the occurrence of thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 22 publications
(17 reference statements)
1
13
0
1
Order By: Relevance
“…The same group also found that TPOAb levels are associated with decreased quality of life, but this study also did not evaluate TgAb levels (Promberger and Hermann et al, 2014). Yet another two studies suggested the role of TPOAb antibodies with the occurrence of symptoms of depression (Pop and Maartens et al, 1998) and fibromyalgia (Dardano and Bazzzichi et al, 2012) pointing to underlying autoimmunity as the cause of morbidity and clinical symptomatology (Dardano and Bazzzichi et al, 2012;Jonklaas, 2017). As shown in linear regression analysis that included TgAb, TPOAb, T3, TSH and thyroid volume, the only predictors for increased symptom load were TgAb levels.…”
Section: Discussionmentioning
confidence: 75%
“…The same group also found that TPOAb levels are associated with decreased quality of life, but this study also did not evaluate TgAb levels (Promberger and Hermann et al, 2014). Yet another two studies suggested the role of TPOAb antibodies with the occurrence of symptoms of depression (Pop and Maartens et al, 1998) and fibromyalgia (Dardano and Bazzzichi et al, 2012) pointing to underlying autoimmunity as the cause of morbidity and clinical symptomatology (Dardano and Bazzzichi et al, 2012;Jonklaas, 2017). As shown in linear regression analysis that included TgAb, TPOAb, T3, TSH and thyroid volume, the only predictors for increased symptom load were TgAb levels.…”
Section: Discussionmentioning
confidence: 75%
“…After screening 4350 articles and excluding duplicates, we reviewed 62 in full text. Of those, 25 articles were included in this study (Figure 1). Nine studies provided data on individuals with overt hypothyroidism, 17 on individuals with subclinical hypothyroidism, and 9 on individuals with thyroid autoimmunity.…”
Section: Resultsmentioning
confidence: 99%
“…It is hypothesized that the dysfunction of the immune system may lead to the reduction of monoamine synaptic availability, which is considered a fundamental mechanism in the pathophysiology of depression [15]. One of the first studies to show the connection between autoimmune thyroid disorders and depression was conducted in 1998 and included 583 perimenopausal women; after adjustment for psychosocial factors it was concluded that women with elevated TPOAb levels (ā‰„100 IU/ml) are at risk for depression [19]. Afterwards the association between MDD and thyroid autoimmunity was further examined in different studies; some of them aimed to reveal the link between HT and depression (see Table 1), while others focused on the connection between increased TPOAb levels and depressive symptoms among the general population (see Table 2).…”
Section: Major Depressive Disordermentioning
confidence: 99%